A New Type of Organic Ferroelectric N-Dehydroabietyl-4-bromobenzamide - Hu, Rong-Hua; Sui, Yan; Wen, Ji-Wu; Luo, Zhi-Gang; Zhong, Long-Jin (Asian Journal of Chemistry, 2015)
A new organic low-molecular-mass compound N-dehydroabietyl-4-bromobenzamide (1) was synthesized using natural biomass dehydro-abietylamine and 4-bromobenzoic acid. Single crystal structure analysis revealed that compound 1 crystallized in a chiral and polar space group P21 and adjacent molecules were hold together by almost straight line N-H···O hydrogen bond chain. Compound 1 exhibits good second-order nonlinear optical and ferroelectric properties. The results indicated a new type organic ferroelectric material derived from natural biomass dehydroabietylamine.